Changes in epilepsy causes of death: A US population study. (16th July 2021) - DeGiorgio, Christopher M.; Curtis, Ashley T.; Hertling, Dieter; Kerr, Wesley T.; Markovic, Daniela
Abstract : Objectives: Since 2000, medical treatment for epilepsy and cardiovascular risk‐reduction strategies have advanced significantly in the United States (US). However, seizure‐free rates remain unchanged, and people with epilepsy are at higher risk than the general population for heart disease and stroke. The purpose of this study is to determine how cardiovascular, epilepsy‐related, and other causes of death are changing in epilepsy in comparison with the US population. Materials & Methods: Changes in the 15 underlying causes of death in epilepsy (ICD‐10 G40‐G40.9) and the US population were analyzed and compared from 2000 to 2018. The CDC multiple cause‐of‐death database was utilized as the primary data source. Changes in the relative proportions for each cause‐of‐death over were evaluated using logistic regression. Results: The proportions of deaths in epilepsy due to heart disease declined 34.4% ( p  < .001), a rate similar to the general population (39.9%). Epilepsy‐related deaths declined 25% as a percentage of all epilepsy deaths ( p  < .001). The proportions of deaths due to stroke and neoplasms increased significantly in epilepsy versus the US population ( p  < .001 linear trend). Conclusions: The reduction in ischemic heart disease in epilepsy is a novel and highly significant finding, which reflects widespread implementation of cardiovascular risk‐factor reduction and treatment in the United States. Reductions in epilepsy‐related deaths are an exciting development which requires further investigation into causality. The increase in deaths due to neoplasms and stroke relative to the US population is concerning, warranting vigilance and increased efforts at recognition, prevention, and treatment.